A novel bifunctional A–D–A type small molecule for efficient organic solar cells. (2nd July 2018) - Song, Jiali; Xue, Xiaonan; Fan, Bingbing; Huo, Lijun; Sun, Yanming
Abstract : A novel A–D–A type small molecule namedDTFBR was designed and synthesized.DTFBR exhibited bifunctional properties when combined with different photovoltaic materials. Abstract : A novel A–D–A type small molecule namedDTFBR was designed and synthesized, in which the fused rings of fluorene, benzothiadiazole and rhodamine were employed as the core donor, bridge acceptor and terminal acceptor unit respectively.DTFBR exhibited a broad absorption band covering the wavelength range from 350 nm to 700 nm and the HOMO and LUMO energy levels are −5.54 eV and −3.68 eV, respectively. Moreover, DTFBR showed bipolar carrier transport behavior, evidenced by the SCLC measurement, where the electron and hole mobilities are calculated to be 2.21 × 10 −4 cm 2 V −1 s −1 and 8.95 × 10 −5 cm 2 V −1 s −1, respectively. The appropriate energy levels and bipolar carrier transport properties makeDTFBR a promising bifunctional photovoltaic material. It can function as the acceptor when it is paired with a poly(3-hexylthiophene) (P3HT ) donor, yielding a power conversion efficiency (PCE) of 3.7%. When [6, 6]-phenyl-C71 -butyric acid methyl ester (PC71 BM ) was used as the acceptor, it can function well as a donor and the corresponding organic solar cells (OSCs) showed a PCE of 2.5% with a high open-circuit voltage ( V oc ) of ∼1.1 V. Our results shed new light on multifunctional photovoltaic material design and OSC application.